Comparative and Equilibrium Studies on Anionic and Cationic Dyes Removal by Nano-Alumina-Doped Catechol Formaldehyde Composite. (26th September 2020) - Karthik, V.; Selvakumar, P.; Sivarajasekar, N.; Megavarshini, P.; Brinda, N.; Kiruthika, J.; Balasubramani, K.; Ahamad, Tansir; Naushad, Mu.
Abstract : Nano-alumina-doped catechol formaldehyde polymeric composite was prepared, characterized, and applied as an adsorbent for the removal of an anionic dye Congo red (CR) and a cationic dye SafraninO (SF), by adsorption process especially from aqueous solutions. Characterizations such as particle size distribution, zeta potential, BET, FTIR, and FESEM-EDAX were carried out for the adsorbent prepared. All experiments were conducted at the batch condition to study the effects of initial dye concentration (CR: 30–90 mg/L and SF: 10–50 mg/L), pH (2–11), temperature (25–55°C), and adsorbent dosage (0.05–0.3 g) on dye removal. The isotherm models (Langmuir, Freundlich, and Temkin) were analyzed for this adsorption work. The kinetic data obtained were analyzed by the pseudo-first-order, pseudo-second-order, Bangham, and Chien–Clayton equations. Dyes adsorption data were well fitted with the Freundlich isotherm equilibrium model and the pseudo-second-order kinetic model. Study results suggested that the nano-alumina-polymeric composite could be an effective adsorbent for anionic dye rather than cationic dye.